2008
DOI: 10.1152/ajpendo.00296.2007
|View full text |Cite
|
Sign up to set email alerts
|

KATPchannel-deficient pancreatic β-cells are streptozotocin resistant because of lower GLUT2 activity

Abstract: Ϫ/Ϫ isolated pancreatic islets also transported less glucose than wild-type ones. Quantification of glucose transporter 2 (GLUT2) protein content by Western blot using an antibody with an epitope in the extracellular loop showed no significant difference in GLUT2 content between wild-type and Kir6.2 Ϫ/Ϫ pancreatic islets. However, visualization by immunofluorescence with the same antibody gave rise to 32% less fluorescence in Kir6.2 Ϫ/Ϫ pancreatic islets. The fluorescence intensity using another antibody, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…STZ is reported to increase oxidative stress (39,40), and the upregulation of antioxidant enzymes could account for the observed resistance. Reduced sensitivity to STZ has been reported for β cells from Kir6.2 -/-mice, which lack K ATP channels (62). The effect is attributed to reduced Glut2 activity, expected to limit the rate of STZ uptake into β cells.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…STZ is reported to increase oxidative stress (39,40), and the upregulation of antioxidant enzymes could account for the observed resistance. Reduced sensitivity to STZ has been reported for β cells from Kir6.2 -/-mice, which lack K ATP channels (62). The effect is attributed to reduced Glut2 activity, expected to limit the rate of STZ uptake into β cells.…”
Section: Discussionmentioning
confidence: 91%
“…The effect is attributed to reduced Glut2 activity, expected to limit the rate of STZ uptake into β cells. However, maximal plasma STZ concentration was significantly lower in Kir6.2 -/-mice than in WT mice (62). Therefore, reduced tissue accumulation could also be explained by the differential STZ plasma concentrations of the 2 genotypes rather than the lower Glut2 activity of the knockout.…”
Section: Discussionmentioning
confidence: 92%
“…Based on several lines of evidence, streptozotocin toxicity toward the ␤-cells depends on the expression of GLUT2. Human islet cells, vs. those of rat or mouse, were resistant to streptozotocin toxicity due to the differential profiles of glucose transporter expression (7); insulinoma cells expressing GLUT2 had increased levels of streptozotocin uptake and susceptibility to streptozotocin-induced destruction in vivo (45); complete GLUT2 deficiency caused the rare Fanconi-Bickel syndrome of kidney syndrome, hepatomegaly, and impaired glucose homeostasis; the GLUT2 Ϫ/Ϫ mice displayed diabetic hyperglycemia and a lack of the first-phase glucose-stimulated insulin secretion, and died at ϳ2-3 wk (54); transgenic expression of glucose transporter genes demonstrated that GLUT2 (but not GLUT1)-reexpressing islets became susceptible to streptozotocin (22); moreover, K ATP channel-deficient (Kir6.2 Ϫ/Ϫ ) pancreatic ␤-cells were insensitive to streptozotocin because of significantly decreased GLUT2 expression on the cell membrane (not necessarily total protein amount) (59). We thus propose that RIP-I/Reg3␤ mice became resistant to streptozotocin due at least in part to diminished level and/or membrane localization of GLUT2, thereby reducing streptozotocin uptake by the ␤-cells.…”
Section: Discussionmentioning
confidence: 99%
“…We thus propose that RIP-I/Reg3␤ mice became resistant to streptozotocin due at least in part to diminished level and/or membrane localization of GLUT2, thereby reducing streptozotocin uptake by the ␤-cells. Although the mechanism of Reg3␤ action within the islet cells is still unclear, decreased GLUT2 expression might be the result of increased p8 expression (see below) or caused by mild hyperglycemia, as chronic exposure to high glucose concentration led to decreased GLUT2 activity (59). Under basal conditions, the decreased GLUT2 level in transgenic islets might contribute to the subtle changes in glycemia, glucose tolerance, and even insulin immunohistochemistry, which require further evaluation using more detailed and dynamic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…While inbred strains differ in their susceptibility to chemically mediated diabetes [35], the majority of the studies designed to better understand the mechanisms of streptozotocin or alloxan-induced diabetes have done so using single gene knockouts [3653]. Missing from these knockout studies, demonstrating either increased sensitivity or resistance to chemically-mediated diabetes, have been direct comparisons to spontaneous T1D.…”
Section: Discussionmentioning
confidence: 99%